Mechanism of the “7•15” debris flow in Baiguoshu gully, Tianquan County, Sichuan Province - Guanglin HUANG; Xiewen HU; Chuanjie XI; Ruichen ZHOU; Kun HE (Zhongguo dizhi zaihai yu fangzhi xuebao)
Compared to wide-gentle debris flows, narrow-steep gully debris flow in small watersheds are characterized by their invisible and sudden nature. Therefore, understanding the mechanism behind such disasters are crucial for engineering management and disaster prevention. This paper presents a case study of the “7•15” debris flow that occurred in Baiguoshu gully, Tianquan County, Sichuan Province in 2021. The process of this debris flow was thoroughly investigated through field surveys, aerial photography, and hydrodynamic simulations using RAMMS. The findings revealed that Baiguoshu gully debris flow was triggered by the cumulative antecedent rainfall and short-term heavy rainfall. The mobilized materials during the “7•15” debris flow consisted of saturated materials upstream that were eroded by floods, as well as landslides triggered by bank erosion along the gully. Subsequently, the amplification of flow discharge caused by blockages and bursting in the main channel resulted in a disaster at the gully outlet and the buried of the Yakang Expressway. The Baiguoshu gully is prone to debris flow occurrences due to the abundance of source materials and favorable hydrodynamic conditions.